The Merchant of Prato— Revisited: Toward a Third Rationality of Information Systems1 - Kumar, Kuldeep; van Dissel, Han G.; Bielli, Paola (MIS Quarterly, 1998)
The failure of SPRINTEL, an interorganizational information system in Prato (Italy), raises a number of interesting questions with regard to the technical-economic and socio-political perspectives that currently dominate the information systems/information technology literature. These questions underscore the importance of developing additional theoretical perspectives in order to better understand the role of information systems in organizations. This article reflects upon these questions and their theoretical foundations in the context of a case study. The case study describes the implementation, usage, and outcome of an interorganizational information system. An analysis is made of the extent to which the technical-economic and socio-political perspectives are sufficient to explain the failure of this system. The outcome of the analysis shows that these two perspectives are insufficient to provide an explanation. Based on the literature from a variety of sources, a third, complementary, perspective is developed. Like the socio-political perspective (Kling 1980), this perspective is also an interactionist perspective. However, instead of focusing on politics and conflict as the primary interaction mode, it focuses on collaboration and cooperation as the key to understanding interaction processes. This perspective introduces a third rationality of information systems in which trust, social capital, and collaborative relationships become the key concepts for interpretation.